DIVERSITY PATTERNS OF RODENT ASSEMBLAGES IN THE NORTH OF FAZAO-MALFAKASSA NATIONAL PARK (TOGO) - Luca Luiselli; AMÉTÉPÉ HOUNMAVO; Delagnon Assou; ABRÉ SONHAYE-OUYÉ; MAWUNYA KOMI GBEMOU; FLORENCE AFI KONKO; ABDOU-RACHAD AYEWA; GABRIEL H. . SEGNIAGBETO; GUILLAUME K. KETOH; Daniele Dendi; Giovanni Amori (European Journal of Ecology, 2023)
The rodent assemblages were studied in different habitat types in the northern part of the Fazao-Malfakassa National Park located in central-western Togo, West Africa. A suite of different methods was applied, including face-by-face interviews with local hunters, live trapping along standardized transects and opportunistic observations. A total of 20 rodent species were recorded based on the surveys carried out in villages, including 6 families and 17 genera. There was a clear gradient pattern in the univariate diversity indices by habitat type: Dominance index was remarkably higher in Urban/plantation than in the other habitat types whereas Evenness index was remarkably higher in gallery forest than in the other habitat types. According to a Canonical Correspondence Analysis, three “ecological groups” (= guilds) of species were formed: a group from wooded habitats (savannahs and semiforests), a group from grassy savannah and a group from urban/plantation habitats. Null model analyses revealed that species tend to non-randomly congregate in some habitat types and/or localities. The ecological implications of these data were presented.